RoboCup 2014: Robot World Cup XVIII - Bianchi, Reinaldo A. C.; Akin, H. Levent; Ramamoorthy, Subramanian; Sugiura, Komei (Lecture Notes in Artificial Intelligence, 2015)
This book includes the thoroughly refereed proceedings of the 18th Annual RoboCup International Symposium, held in Joao Pessoa, Brazil, in July 2014.The 36 revised papers were carefully reviewed and selected from 66 submis-sions and include 11 champion-team papers, three special-track papers on open-source hardware and software, nine papers on the advancement of the RoboCup leagues track, and three best papers. The contributions present current research and educational activities in the field of robotics and artificial intelligence with a special focus on the interaction between robots and humans.